2020
DOI: 10.1002/cplu.202000517
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Porphycenes: Synthesis, Spectroscopy, Photophysics, and Tautomerism

Abstract: Six porphycenes have been synthesized, bearing one, two, or three fluorine atoms attached directly to the 18‐π‐electron system at the meso positions. These novel compounds have been characterized by structural, electrochemical, and spectral techniques, combined with quantum chemical calculations. In three fluoroporphycenes, the unsymmetric substitution pattern leads to the presence of two nonequivalent trans tautomeric forms. They have been identified using electronic absorption, emission, and magnetic circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…A similar effect has been recently reported for 9-fluoroporphycene. 22 Our assignments agree with the results of a theoretical paper in which the absorption of 9-amino-2,6,12,17-tetraphenylporphycene has been modelled using the nuclear ensemble method. 49 The authors concluded that the first absorption band originates from trans1, but the second band is dominated by transition from trans2.…”
Section: Theoretical Predictions Of the Relative Energies Of Tautomer...supporting
confidence: 85%
See 2 more Smart Citations
“…A similar effect has been recently reported for 9-fluoroporphycene. 22 Our assignments agree with the results of a theoretical paper in which the absorption of 9-amino-2,6,12,17-tetraphenylporphycene has been modelled using the nuclear ensemble method. 49 The authors concluded that the first absorption band originates from trans1, but the second band is dominated by transition from trans2.…”
Section: Theoretical Predictions Of the Relative Energies Of Tautomer...supporting
confidence: 85%
“…Photophysical studies demonstrate that both, amino and nitroporphycenes behave similarly to other unsymmetrically substituted porphycenes, such as 9-acetoxy 18,50 or 9-fluoro 22 derivatives. In the ground electronic state, two trans tautomers of similar energy coexist, whereas in S 1 the equilibrium is shifted towards the structure which was already more stable in S 0 ( trans 1 in amino-, trans 2 in nitroporphycenes).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, parent porphycene (1) and its 2,7,12,17-tetra-tert-butyl derivative (2) have very similar spectral and photophysical characteristics [21], but differ by the absence/presence of the substituent 'shield'. In contrast, the same shield is present in 2 and 3 (9-fluoro-2,7,12,17-tetra-tert-butyl-porphycene), but now the spectral parameters differ somewhat [26]. Finally, the three porphycenes selected for this study have similar redox properties, which is crucial when photodestruction efficiencies are to be compared.…”
Section: Introductionmentioning
confidence: 92%
“…Another kind of PS is porphycenes, which are isomers of porphyrins. Their unique aromatic structure provides them with different photophysical properties than those observed for the porphyrins, as a stronger absorption at 600-700 nm and a strong fluorescence [65] . Although the less, there are some examples of cationic porphycenes being used against bacteria, as Ruiz-González et al research, whom synthesized two porphycenes (57 and 58, Fig.…”
Section: Other Cationic Photosensitizersmentioning
confidence: 99%